Effect of blending time and crumb rubber content on properties of crumb rubber modified asphalt binder - Mashaan, N.S.; Ali, A.H.; Karim, M.R.; Abdelaziz, M. (2011)
The increasing use of crumb rubber modifier in flexible pavements justifies the necessity for a better understanding of its physical and rheological properties as well as its elasticity behaviour. Basically the performance and properties of rubberised asphalt binder are influenced by the blending conditions and crumb rubber content. In this study, the laboratory investigation was conducted on crumb rubber modified asphalt binder properties as a function of two blending times (30 minutes and 60 minutes) and five crumb rubber contents (4, 8, 12, 16 and 20 by weight of asphalt binder) at mixing temperature of 180Â°C. Statistical analysis using two-way ANOVA was conducted on the results to evaluate the significance of rubber contents and blending times. The rubberised asphalt binder was evaluated in terms of binder elasticity and rutting resistance at high temperature. The results indicate that the crumb rubber content had a significant effect on G*/ sin (Î´) at 76Â°C. The higher crumb rubber content appears to dramatically increase the elastic recovery and ductility. Statistical analysis showed significant effect of crumb rubber content in influencing the ductility, elastic recovery and G*/ sin (Î´) values. Whereas the blending time do not appears to significantly affect the ductility, elastic recovery and rutting factor (G*/ sin (Î´)) of the CRM asphalt binder. The asphalt binder with higher crumb rubber content and longer blending time of 60 minutes exhibited a higher value of elastic recovery. This indicates that crumb rubber modified asphalt binder has better resistance to rutting as compared to conventional asphalt binder.